Factibilidad de la creación de una micro startup especializada en nutrición en el cantón Bolívar - Zambrano Solórzano, Gema Valeria (2019)
This research was based on knowing the feasibility that a micro startup specialized in nutrition in Bolivar Canton would have for which a target market study was developed through a survey, to know the tastes and preferences of those who could be potential customers, as a result it was obtained that the micro startup would have a favorable and attractive acceptance, since it was evidenced in the acquired data that 100% of people surveyed would be willing to include this service to their daily life, highlighting that as the main activity they would have to offer the client a personalized food service, with different options for all tastes and preferences aimed at their benefit, comfort and health, with a medical service and home delivery which leads to practicality with people who work and do not have time to prepare food and this covers the demand studied which is the Population Economically Active of Bolivar Canton, the technical study was also formulated in which the operational capacity and the processes necessary for the financing and operation of the micro Startup were determined, an economic-financial study for the implementation was carried out, and the result was that the investment for this micro venture will have an initial capital of $ 80,000, 37.5% will be the investment of two shareholders and 62.5% will be financed through the National Finance Corporation.